Strengthening SEHATI self-declare halal certification in South Kalimantan: Roles, constraints, and field practices of Halal Product Process Companions - Makiah, Zulpa; Sauri, Supian; Sahal, Lutpi (Journal of Islamic Economics Lariba, 2026)
IntroductionIndonesia’s halal certification regime has expanded rapidly following the Halal Product Assurance Law, positioning halal assurance as both a consumer protection instrument and a strategic requirement for micro and small enterprises. To accelerate inclusion, the Free Halal Certification Program (SEHATI) applies a self-declare pathway that depends heavily on Halal Product Process Companions to facilitate verification and validation at the grassroots level. However, implementation performance varies across regions, raising questions about how frontline facilitation shapes program outcomes in geographically dispersed provinces such as South Kalimantan.ObjectivesThis study examines how Halal Product Process Companions operationalize SEHATI in South Kalimantan by analyzing their roles, constraints, and adaptive practices in assisting micro and small enterprises through the self-declare halal certification process. It also explores the structural and technical factors that contribute to implementation gaps between program targets and realized certification outcomes.MethodThis research used a qualitative field research design. Data were collected through semi-structured, in-depth interviews with 37 Halal Product Process Companions selected purposively across districts and cities in South Kalimantan. Secondary data were obtained from relevant regulations, institutional reports, and prior studies. The analysis followed an iterative qualitative procedure involving data reduction, data display, and conclusion drawing.ResultsThe findings show that Halal Product Process Companions function as hybrid implementers who perform two interdependent roles: educating micro and small enterprises about halal requirements and providing technical support for verification, validation, and digital submission. Implementation is constrained by administrative complexity, unstable internet connectivity, platform limitations, and uneven institutional support. At the enterprise level, limited digital literacy, uneven halal knowledge, and weak responsiveness delay certification completion and increase facilitation workload. These conditions explain why SEHATI outcomes may fall short of targets despite simplified procedures.ImplicationsThe study highlights that SEHATI effectiveness depends on integrated capacity building and institutional support, including improved digital infrastructure, simplified workflows, stronger training, and structured supervision to sustain both accessibility and certification credibility.Originality/NoveltyThis research contributes field-based evidence on self-declare halal certification implementation by centering Halal Product Process Companions as frontline intermediaries whose dual roles and constraints shape the practical success of SEHATI at the provincial level.